Career Development Opportunity Cures for the Impairment Effect of Careerist Orientation on Organizational Citizenship Behaviours: Empirical Evidences form Project Based Employees Working in Non-profit Making Organization - Bhattarai, Ganesh; Pokharel, Dhruba Raj; Budhathoki, Prem Bahadur (Dristikon: A Multidisciplinary Journal, 2020)
This study was carried out to examine the direct impact of employees‘ careerist orientation and career growth opportunities on their organizational citizenship behaviours (conscientiousness and altruism) as well as role of career growth opportunities in the relationship between careerist orientation and organizational citizenship behaviours (conscientiousness and altruism). 268employees working in non-profit making projects in Kathmandu valley were surveyed and analyzed. Quantitative analysis of multi-source measured perceptual data revealed that (1)employees‘ careerist orientation negatively impacts on organizational citizenship behavior (conscientiousness and altruism), (2) and career growth opportunities positively impacts on organizational citizenship behaviors (conscientiousness and altruism), and (3) employees career growth opportunities cure their harmful impact of careerist orientation on organizational citizenship behaviour (conscientiousness and altruism). Moreover, this study tested the different forms (effect sizes) of interactive effect of employees‘ careerist orientation and career growth opportunities to predict their organizational citizenship behaviours (conscientiousness and altruism). For example, it was tested that a relatively strong marginal negative prediction of careerist orientation on organizational citizenship behaviours (conscientiousness and altruism)was for those employees who perceive a low level of career growth opportunities. A number of theoretical and practical implications are suggested.